The current management of alveolar soft part sarcomas. Issue 31 (6th August 2021) - Chang, Xiaojing; Li, Yuehong; Xue, Xiaoying; Zhou, Huandi; Hou, Liubing
Abstract: Objective: Alveolar soft part sarcomas (ASPS) which has high potential ability of metastasis, is a rare and slowly growing malignant tumor, and mainly primary localized in limbs. To date, little is known about the best treatment of ASPS. This study aims to review the current management and advance of ASPS. Methods: WANFANG MED ONLINE, CNKI, and NCBI PUBMED were used to search literature spanning from 1963 to 2020, and all cases of ASPS about "ASPS, diagnosis, treatment, surgery, radiotherapy, chemotherapy, target therapy or immune therapy" with detailed data were included. Results: Complete surgical resection remained the standard management strategy, radiotherapy was reported to be used for the patients of micro- or macroscopical incomplete residue or the surgical margin was questionable. Chemotherapy was controversial. Some target drugs and immune checkpoint inhibitors had produced antitumor activity. Conclusion: Complete surgical resection is the cure treatment for ASPS, and adjuvant chemotherapy is not recommended excepted clinical trials. For the patients with micro- or macroscopical incomplete residue, radiotherapy should be appreciated. Furthermore, for recurrence, distant metastasis, and refractory of ASPS, combination therapy, especially combination with multiple target agents and/or immune checkpoint inhibitors may prolong survival time.